Análisis del deterioro del “Área Minera Valle Hermoso” vinculada a la NIIF 6, aplicando un método de valorización según la NIC 16, ubicada en el cantón Pelileo – provincia de Tungurahua. - Maroto Criollo, Alba Aracelly (2019)
The present integrative project discussed an analysis on the spoilage of the value of the assets in which, petrean materials were found for exploitation., where countable and tributary impacts were demonstrated; Project that was applicable in the “Valle Hermoso” Mining Area, located in Pelileo’s Canton ,Province of Tungurahua. The problem detected in the area, is the ignorance of the utilization of accounting and financial standards related to activities of exploring and evaluation of natural resources, wich did not allow considered the spoilage of the assett and applying a model of re-evaluation. The main goal of this project, consists in determining the spoilage that suffers the mining área, applying methods of real valorization according to IAS16, standard that allowed knowing its reasonable value in accounting books. The inmersed phases in the process of mining operation, that begin from prospection or search for clues of minerals, the exploration that determines the type, quantity and volume of minerals, the exploitation or extraction, the benefit, the refinement or adjusting of the material for commercialization and finally the closing of mines. Then once analyzed the exploitation mining phasess, it was detected that existed factors that affected the economic activity, same factors that give recognition to the existence of spolaige , valorized for $20.915,64; Value calculated considering the económica valuation value of the assets in front of the supplies to explode, its reasonable value by use of the addition of the incurred costs for its starting; Cost and expenses valorized commercially, like also exhaustion, items that were applicable when recognizing the existence of internal and external factors that reflect indications of spoilage. The application of a deductive methodology helped to conclude that the project is favorable for the company, intervening also the analytical methodology that allowed disaggregating the subject matter step by step and to analyze them for separated, in order to determine their effects and causes with techniques of observation applied right into the área of study. This countable tool will helps to maintain opportune real information on the financial company situation, coming from great benefit for the administrators of the mining area at the time of making decisions, like so it will helps economically to tax decrease.